Determination and optimization of the effect of cutting parameters and workpiece length on the geometric tolerances and surface roughness in turning operation - (:unkn) unknown (My University, 2011)
In this work, the geometric tolerance and surface quality of an aluminium piece produced by turning is analysed. The effect of the length and diameter of working piece, cutting depth and feed were also investigated. The cutting speed, which is an important machining parameter, was kept constant in this study. Going from past works experience the effect of cutting speed was ignored. Statically method of Taguchi was used in this work in order to obtain more reliable and optimum results. By this method, time and cost savings were made, and the test results were optimized. The relation between the dependent and independent variables were also modelled by regression analysis. The results showed that cutting force, surface roughness, cylindricity and vibration were minimised in machining process and production quality was improved. © 2011 Academic Journals.
Keywords: Geometric tolerance; Regression analysis; Surface quality; Taguchi method; Turning